Integrating the I-CLEANED tool into Vietnamese university curricula: A training of trainers - Dao, Thi Thu Hang; Mema, Emmanuel; Notenbaert, An Maria Omer; Atieno, Mary (International Center for Tropical Agriculture, 2024)
The Alliance of Bioversity International and CIAT (ABC) is a co-implementor of the CGIAR Initiative on Sustainable Animal Productivity for Livelihoods, Nutrition, and Gender Inclusion (SAPLING), which aims to enhance livestock productivity while ensuring environmental sustainability. Environmental awareness and evidence generation training is one of the ways the initiative is working to meet its objectives across the seven focus countries. On 25–26 October 2024, an in-person training event on the Inclusive and Comprehensive Livestock Environmental Assessment for improved Nutrition, a secure Environment and sustainable Development along livestock value chains (I-CLEANED) tool took place in Vietnam to explore gaps in university curricula and train the first batch of trainers in academia.